The Hearing Voices Movement as Postmodern Religion-Making: Meaning, Power, Sacralization, Identity. (4th June 2017) - Powell, Adam
Abstract : Over the past 40 or 50 years, scholars of religion have frequently attempted to use the tools of social science to analyse, describe, and explain the relevance and persistence of religion in the modern world.  With the bold predictions of the secularization thesis as their stimuli, many sociologists and anthropologists preferred to focus on the underexplored, marginalised, or otherwise unexpected expressions of religion within those ostensibly secularising contexts.  Such studies have led to an abundance of theories and accompanying terms: 'implicit religion', 'vernacular religion', 'vicarious religion', 'lived religion', 'popular religion', and 'folk religion'.  Without choosing any one of these, but owing much to their shared – arguably postmodern – themes of commonplace sacrality and personal empowerment, this paper seeks to explore the possibility of the Hearing Voices Movement (HVM) as an example of religion-making.  HVM is a growing force of 'voice-hearers' from at least 28 countries who have formed user-led networks for activism and mental health recovery.  More importantly, it is argued that HVM blends meaning-making, postmodern notions of identity in relation to power structures, and ritual embodiment, resulting in a striking example of sociologist Hans Mol's notion of religion as a sacralizing process.